2017
DOI: 10.18632/oncotarget.17973
|View full text |Cite
|
Sign up to set email alerts
|

M2 tumor-associated macrophages produce interleukin-17 to suppress oxaliplatin-induced apoptosis in hepatocellular carcinoma

Abstract: M2 macrophages are a major component of the tumor microenvironment and are important promoters of tumor occurrence and progression. In this study, we detected large numbers of M2 macrophages in hepatocellular carcinoma tissues using immunohistochemistry and immunofluorescence. Moreover, upon oxaliplatin treatment, the M2 macrophages overexpressed interleukin-17, an important inflammatory cytokine, and thus inhibited oxaliplatin-induced apoptosis. By knocking down the interleukin-17 receptor and lysosome-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…Moreover, CMA confers resistance to cancer treatment through cell type–specific mechanisms. For instance, CMA prevents apoptosis and contributes to resistance to oxaliplatin in hepatocellular carcinoma by degrading the apoptosis trigger cyclin D1, 19 and to irradiation by degrading HMGB1 20 . Furthermore, active degradation of the acetyltransferase p300/CBP by CMA confers resistance to 5‐fluorouracil in colorectal cancer 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CMA confers resistance to cancer treatment through cell type–specific mechanisms. For instance, CMA prevents apoptosis and contributes to resistance to oxaliplatin in hepatocellular carcinoma by degrading the apoptosis trigger cyclin D1, 19 and to irradiation by degrading HMGB1 20 . Furthermore, active degradation of the acetyltransferase p300/CBP by CMA confers resistance to 5‐fluorouracil in colorectal cancer 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is an inverse correlation between cyclin D1 expression levels and CMA activity [ 83 ]. There is still a long way to go to actually prove that cyclin D1 is a CMA substrate, but whether this modulation occurs through a direct or indirect mechanism, the fact is that CMA affects cyclin D1 levels.…”
Section: Cma Control Of Cell Cycle In Distinct Cellular Contextsmentioning
confidence: 99%
“…Tumor-associated macrophages are the major components of tumor inflammatory infiltration and are key mediators between tumors and inflammation (Mantovani et al, 1992). Guo et al found that M2 macrophages in the HCC microenvironment can secrete large amounts of IL-17 and inhibit oxaliplatin-induced apoptosis by activating chaperone-mediated autophagy (Guo B. et al, 2017). Tumor-associated neutrophils are also an important part of the tumor microenvironment and can promote various biological activities of tumors (Galdiero et al, 2013).…”
Section: Discussionmentioning
confidence: 99%